PREDIKSI TINGKAT KERUSAKAN BATANG ROTOR PADA MOTOR INDUKSI BERDASAR ANALISIS CIRI ARUS CATU DAN CIRI GETARANG - Nurhadi, Indra; Abidin, Zainal; Darmawan, Haris (Mesin, 2001)
Typically, mechanical vibration signature analysis is one of the essential steps in predictive maintenance activity for rotating machines. This paper discusses a study on the use of motor current signature analysis as a complement to the vibration signature analysis in identifying broken rotor bar in 3-phase induction motors. From literature study[5, 6, 7, 8, 9, 10, 11], it was summarized that the presence of rotor bar faults can be detected through the increase in (1x rpm ± Fs x p) side-bands amplitude of mechanical vibration. In addition, this type of fault is also signified by the increase in (1 ± 2s)Fl side-bands amplitude of motor current. Furthermore, the amplitude of the left side-band of supply current spectra can be used to estimate fault severity.To prove the validity of the theory and to study its feasibility for practical use, experimentation was conducted using a small 2-pole motor of ¼ hp, coupled with a generator. Spectral analysis performed on motor current and body vibration shows results as predicted by the theory.